Internalization Of Sharia Economic Perspective Based On Creative Economy On Coffee Commodities in Enrekang Regency, South Sulawesi. - Nur Aini; Nuringsih, Nuringsih; Lismawati, Lismawati (International Journal of Economics, Business and Innovation Research, 2025)
The creative economy is a sector that prioritizes the use of creativity, knowledge, and skills to produce products and services with high added value. From the perspective of sharia economics, the creative economy is not only seen in terms of its economic value, but must also be in accordance with sharia principles, such as justice, welfare, and sustainability. This study uses a qualitative approach with observation and interview methods. The understanding and application of sharia economic principles in coffee business activities in Bone Bone Village can be seen from several indicators, such as the level of public understanding of sharia concepts, the extent to which these principles are applied in coffee business practices, and their impact on the sustainability and welfare of farmers. Based on the results of research and observations, the following is an overview of the extent to which the people in Bone Bone Village understand and apply sharia economic principles in their coffee business activities. This study aims to explore the application of sharia economic principles in developing a creative economy in coffee commodities in Bone-Bone Village, Enrekang Regency. The main focus of this study is to analyze how the internalization of sharia economic principles such as justice, transparency, and the prohibition of usury can be applied in the local coffee industry to create added value and sustainability for rural communities. The research method used is qualitative with a case study approach, which includes interviews with coffee farmers, coffee entrepreneurs, and the surrounding community. The results of the study show that the application of sharia economics in the production and marketing of coffee based on the creative economy can improve the quality of life of coffee farmers and develop coffee products that are more valuable in the local and global markets. However, challenges in its implementation include a lack of a deep understanding of sharia economics and the limitations of marketing infrastructure. This study recommends strengthening sharia education and marketing digitalization as a solution.